Survey of Student Views about Factors Affecting Students Attendance in Classrooms in Sabzevar University of Medical Sciences Iran - Elham Azmoudeh; Maryam Dolati; Elham Farzadmanesh; Ali Asghar Khosro Abadi; Mohammad Hassan Rakhshani (Kerman University of Medical Sciences, 2013)
Background & Objective: Absence of students from the classroom is one of the problems in the medical sciences in recent years Failure to attend classes disrupts the dynamic teachinglearning environment and causes this environment to become boring and unpleasant The aim of this study was to evaluate medical students views on factors affecting their presence in classrooms in Sabzevar University of Medical Sciences Iran in 2011 Methods: 288 students participated in this crosssectional study For data collection a questionnaire containing 28 questions in 5 Likert types was used Results: 215 female (747%) and 73 male students (253%) participated in this survey 79% of participants were single The highest score was in the area of teacher characteristics (013 ± 076) The next highest scores were the course features (018 ± 0755) physical environment (017 ± 0747) and the student characteristics (014 ± 0747) respectively Conclusion: It can be concluded from the findings of this study that the most important factor involved in the increased attendance in classroom is teacher characteristics such as the content presented in the classroom or the teacher s interesting speech Course features or class time are also important Given this factor we hope educators and planners improve the teaching and learning process through the increased presence in classrooms